CLIMATE AND ANTHROPOGENIC IMPACTS ON EARTH SURFACE PROCESSES IN THE ANTHROPOCENE - Beylich, Achim A.; Tarrio Vazquez, Daniel; Li, Dongfeng; Oliva, Marc; Marteles, Mario Morellón (Elsevier, 2025)
Climate and Anthropogenic Impacts on Earth Surface Processes in the Anthropocene outlines our current understanding of the effects of ongoing and accelerated environmental changes on Earth surface processes and details the systematic and quantitative methodology on the actual drivers of these processes. This book covers various geomorphological process domains and a wide range of terrestrial surface environments on Earth. It provides a broad spectrum of advanced techniques and methods of data collection and generation, together with various approaches and methods of data analysis and geomorphologic modelling. This book is a valuable resource for upper-level undergraduates, graduates, and academics studying Earth surface processes, as well as researchers and professionals in needing a comprehensive overview of Earth surface process change and influence during the Anthropocene